Desenvolvimento e padronização de um ensaio in vitro para determinação da potência neutralizante de antivenenos antibotrópicos - Letícia Lopes de Souza (2019)
Accidents with poisonous snakes are a major health hazard in tropical countries. Bothrops genus is responsible for more than 70 % of snakebites in Brazil. Immunotherapy is the only recommended specific treatment against snake toxins approved by World Health Organization and the production of therapeutic antivenoms require quality control tests to determine their neutralizing potency. Currently, these controls are performed by lethality neutralization assay using experimental animals. The aim of this work was to develop an in vitro alternative test for antivenom pre-clinical evaluation. In this sense, we designed a cell viability assay using different amounts of low and high potency anti-bothropic sera, preincubated with B. jararaca venom, for assessing the antivenom capacity to protect the cells against venom toxic effects. We found that high potency sera are more effective in neutralizing the cytotoxicity when compared to low potency sera, which is in accordance to their pre-determined in vivo potency. Considering sera in vitro inhibitory concentration able to prevent 50% cell death (IC50), a cut-off point was determined to discriminate low and high potency sera. Cell viability assay was suitable for sera potency discrimination, pointing out the potential of the in vitro method to determine neutralizing antivenom antibothropic potency during the production process. This assay was also used to evaluate the sera efficacy to neutralize envenomation local effects, simulating the real conditions of treatment. Bothrops snake venoms were incubated to cells and after different time points, the antivenom was added. Serum neutralizing efficacy shows interspecific variations and it is time-dependent. Our data provide insights for the development of an in vitro method which can reduce the number of animals used in the antivenoms evaluation, following the world trend of replacing animal experimentation.